2018
DOI: 10.24953/turkjped.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

A case of steroid-resistance Hashimoto's encephalopathy presenting with sensorimotor polyneuropathy

Abstract: Hashimoto's encephalopathy (HE) is a rare, auto-immune disease characterized by symptoms of acute or subacute encephalopathy associated with increased anti-thyroid antibody levels. The course of most HE cases is relapsing and remitting, which is similar to that of vasculitis and stroke. Steroids are the first line treatment in HE. In steroid non-responders other immunomodulatory therapies or plasmapheresis could be applied. We report a case of steroidresistance HE with sensorimotor polyneuropathy, as a rare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…After biopsy, it was found that the lesion was not a tumor, and HE was finally confirmed (Uwatoko et al, 2018). Patients with HE can also present with unusual symptoms such as pseudobulbar palsy, sensorimotor polyneuropathy, catatonic symptoms, vertigo, muscle weakness, chorea, opsoclonus, and a trigeminal neuralgia type headache, among others (Beckmann et al, 2011;Salazar et al, 2012;Sharan et al, 2015;Ueno et al, 2016;Karthik et al, 2017;Emeksiz et al, 2018;Oz Tuncer et al, 2018). Rapidly progressive dementia, as a common manifestation of HE, makes it necessary to distinguish HE from other diseases caused by vascular, infectious, toxic-metabolic, and autoimmune factors, metastasis/neoplasia, iatrogenic/inborn errors of metabolism, neurodegenerative diseases, and systemic diseases/seizures (Paterson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…After biopsy, it was found that the lesion was not a tumor, and HE was finally confirmed (Uwatoko et al, 2018). Patients with HE can also present with unusual symptoms such as pseudobulbar palsy, sensorimotor polyneuropathy, catatonic symptoms, vertigo, muscle weakness, chorea, opsoclonus, and a trigeminal neuralgia type headache, among others (Beckmann et al, 2011;Salazar et al, 2012;Sharan et al, 2015;Ueno et al, 2016;Karthik et al, 2017;Emeksiz et al, 2018;Oz Tuncer et al, 2018). Rapidly progressive dementia, as a common manifestation of HE, makes it necessary to distinguish HE from other diseases caused by vascular, infectious, toxic-metabolic, and autoimmune factors, metastasis/neoplasia, iatrogenic/inborn errors of metabolism, neurodegenerative diseases, and systemic diseases/seizures (Paterson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%